Construction of organometallic trefoil knots and one-dimensional chains featuring half-sandwich Cp*Rh corner units and an abnormal zwitterion ligand. Issue 2 (16th November 2020) - Gao, Xiang; Cui, Zheng; Lin, Yue-Jian; Jin, Guo-Xin
Abstract : An abnormal flexible O-coordinated zwitterion ligand L shows self-adaptive conformation behaviour in chemical self-assembly. Two trefoil knots were obtained with C-shaped ligand L and two novel 1D chains were obtained with Z-shaped ligand L . Abstract : An abnormal O-coordinated zwitterionic ligand L was designed and applied to construct intricate supramolecular elements based on half-sandwich Cp*Rh units. This zwitterionic ligand has two stable conformations, C- and Z-shapes, which undergo self-adaptation when assembled with different building blocks. Two trefoil knots were obtained using dinuclear building blocks (Cp*Rh)2 (1, 4-DHATQ)(OTf)2 and (Cp*Rh)2 (DHNAD)(OTf)2, in which the ligand L was observed to adopt its C-shaped conformation. In addition, two novel one-dimensional chains were constructed using the building blocks (Cp*Rh)2 (1, 5-DHATQ)(OTf)2 and (Cp*Rh)2 (DHNTQ)(OTf)2 . Only the Z-shaped conformation of ligand L was observed in these two 1D chains.